EFFICACY OF BULB EXTRACTS OF ALLIUM CEPA VARIETIES (RED, WHITE AND SMALL ONION): AN IN VITRO ANTIFUNGAL AND ANTIOXIDANT ACTIVITY - PONNULAKSHMI R; EZHILARASI BALASUBRAMANIAN S (International Journal of Pharma and Bio Sciences, 2013)
The study was performed to evaluate the efficacy of different extracts of bulb of the Allium cepa varieties on antifungal and antioxidant activity. The extracts were prepared with aqueous, ethanol, chloroform and petroleum ether and subjected for preliminary phyto-chemical, antioxidant and antifungal activity. The total ash and water content, organic, inorganic were evaluated along with the different extracts of onion bulb. Total phenolic content were analyzed by HPLC method. The presence of primary and secondary metabolites such as carbohydrate, proteins, alkaloids, phenolic compounds, saponins was confirmed through preliminary phyto-chemical analysis. DPPH free radical, nitric oxide, superoxide anion radical scavenging assays showed strong antioxidant activities with increase in concentration of bulb extracts of the aqueous, ethanol, chloroform and petroleum ether fractions of the three onion varieties. Antifungal activity was assessed by the paper disc agar diffusion method. The results of the antifungal activity showed that among the onion varieties analyzed, the small onion exhibited strong fungal growth inhibition in its aqueous, chloroform and petroleum ether extraction while white onion is effective in its ethanolic extract and red onion is effective in its chloroform extract. Screening of antioxidant and antibacterial activity performed on A.cepa bulb extracts shows that they are endowed with potentially exploitable free radical scavenging and antifungal activity. These results showed that onion bulb can be a source of compounds that can serve as templates for future fungicides against Aspergillus niger, Aspergillus, fumigates, Candida albicans and Aspergillus flavus. Hence, bulb extracts of A.cepa varieties could be used as an easy accessible source of natural antioxidants, and antifungal agent making it one of the potent therapeutic phytomedicines.